Generativity in Life Review: Discovering Life Lessons and Wisdom in Naturalistic Intergenerational Conversations. (17th December 2021) - Chilton, Patricia; Woolverton, Cindy; Glisky, Elizabeth; Mehl, Matthias; Grilli, Matthew
Abstract: According to the theory of generativity, one would expect older adults to inherently feature life lessons in naturalistic conversations with younger adults. Little though, is known about the process of these conversations, and to what extent they convey wisdom characteristics. In this project, intergenerational conversations between university students and older adults living in assisted and independent living communities were analyzed to identify life lessons within older adults' informal life reviews. In the original study, 37 young and 52 older adults engaged in an intergenerational interaction as part of an undergraduate course. These conversations were recorded with participants' consent, and transcribed with identifying information removed. For the current project, we analyzed 15 of these recorded conversations, averaging 46 minutes each between 10 students and 5 older adults to (1) develop a coding scheme and procedure to examine life lessons in intergenerational conversations, and (2) investigate whether wisdom characteristics are embedded into life lessons shared in this context. On average, each older adult referenced 4 life lessons (SD = 2) per conversation, which were coded for the following constructs: meaning making, personal growth, emotional valence, wisdom characteristics, life lesson type, and autobiographical memory type. Exploratory analyses suggest life lessons are inherently integrated into naturalistic intergenerational conversations, and that reflectivity is the most frequently expressed wisdom characteristic. This supports previous research identifying reflectivity as key to wisdom, and to the process of generativity. Further analysis is needed to illuminate the value of intergenerational conversations, particularly in a time of age segregation and ageism.